Awareness of Cash Waqf among the Malaysian Muslims / Wan Musyirah Wan Ismail … [et al.] - Wan Ismail, Wan Musyirah (2015)
Waqf is an Arabic word that comes from the root word Waqafa which means stop. Waqf is not compulsory, but it is much needed in Islam. One of the types of Waqf is Cash Waqf. Cash Waqf is a collection of fund to support services to mankind in the name of Allah. This study is looking into the awareness of Cash Waqf among Muslims in Malaysia. The objectives of this study are to investigate how far Muslims in Malaysia are aware and have knowledge about Cash Waqf and to identify important factors related to Cash Waqf that can influence the public to contribute in Cash Waqf. A set of questionnaires were distributed to 240 people in Klang Valley. Besides that, interview had also been conducted to get a clear picture on implementation of Cash Waqf in Selangor by Perbadanan Wakaf Selangor. The research found that 40% from 240 respondents had knowledge about Cash Waqf. A small percentage of only 13.8 % involved in Cash Waqf. However, 93.8% from the respondents were interested to learn more about Cash Waqf. About 85% of them agree that the knowledge of institution of Cash Waqf is an important factor to increase Muslim’s awareness to Cash Waqf, followed by the knowledge of the process of collection and distribution of Cash Waqf and the role of Cash Waqf. Thus, we assume that when people know about the institutions of Cash Waqf in their country, they would be more interested to get more information about Cash Waqf and gain more knowledge about the process of Cash Waqf. Furthermore, this will encourage Muslims to contribute in Cash Waqf.